The relationship between workplace environment and the employee performance in Kendek Group of Companies / Afifah Diyana Zahari - Zahari, Afifah Diyana (Faculty of Business and Management, 2019)
This study is to investigate the effects of workplace environment on the employees’ performance in Kendek Group of Companies. Four objectives have been determined in order to achieve the purpose of this study. First is to investigate the relationship between physical workplace factors and the performance of Kendek Group of Companies’s employees. Second objective is to investigate the relationship between psychosocial workplace factors and the performance of Kendek Group of Companies’s employees. Third, to investigate the relationship between work life balance and the performance of Kendek Group of Companies’s employees. Fourth, to identify the most significant factor of workplace environment that effects the performance of Kendek Group of Companies’s employees. The population of this study consists of 94 employees from Kendek Group of Companies, while the sample consists of 76 respondents. The data were collected by distribute 76 questionnaires were used in the study. The questionnaires designed based on three independent variables that are expected to affect employees’s performance which are physical factor, psychosocial factor and work life balance. To analyses the data, descriptive, correlation, and regression analyses was used. Hence, the results from this study reveal that there is a positive relationship between three independent variables which are physical factor, psychosocial factor and work life balance towards employees’performance. In addition, there are many others factors that may effects the employees’ performance which are not included in this research intend to suggests to include others factors as discuss in chapter 5. The sample of this study only limited to the employee that are working in Kendek Group of Companies.